UPAYA ORANG TUA DALAM MENGATASI REMAJA PUTUS SEKOLAH (STUDI DI DUSUN TUMPUAN HATI DESA BENTUNAI KECAMATAN SELAKAU) - Safitri Safitri; Nuraini Asriati; Supriadi Supriadi (Universitas Tanjungpura, 2017)
AbstractThe general problem in this research is What Are The Efforts Of Parents in Overcoming Drop out Teenagers in the Hamlet Tumpuan Heart of Bentunai Villages at Selakau Subdistrict. The research method used is descriptive method with qualitative research form. Techniques data collection using direct observation techniques, direct communication, and documentary study with tools of data collection such as observation guides, interviews, and documentation. From the results of the research can be concluded that the efforts of parents in overcoming teenagers drop out of school is still less than optimal. This resulted from the parents efforts to motivate children and the control of children is very less because the parents of busy work, even though parents force children to school and the result of children still choose not to continue school. Parents have provided suggestion and advice to be able supervise and control the child’s when at home, has been trying to foster and remind the child’s even though not maximized. Not supporting the role of parents is also accompanied the attitude of children also less excited or less enthusiastic to school or study home, so happened the problem drop out of the school. Keywords: Efforts of parents, Teenagers, Drop Out of School